Increasing Care for Patients with Mental Disorders Thought Community Empowerment: A Literature Review - Yosua Aldrin Kaligis; Shanti Wardaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Families and people with mental illnesses require community empowerment. When the environment is not empowered, it will have the impact of decreasing productivity levels. To realize mental health and public concern for people with mental disorders, it is necessary to make strategic efforts by developing mental health promotion programs as a preventive effort and increasing community empowerment to support mental health. aims to determine community empowerment in increasing care for patients with mental disorders. The following bibliographical databases were searched to identify potentially relevant documents: Google Scholar, Pubmed, and Proquest publications, 2017–2022. Findings from studies were extracted and aggregated, guided by the Joanna Briggs Institute (JBI). Literature review uses the PubMed, ProQuest, and Google Scholar databases. Keywords: "community empowerment"; "community concern"; "community involvement"; "mental disorder." A total of 43,253 articles were obtained. The final results obtained were 12 articles that met the review requirements. The result is that community empowerment in the form of programs or services regarding health in the neighborhood increases public awareness of people with mental disorders. empowerment carried out by the community directly, such as mental health campaigns, discussions, training, and providing facilities and means to support people with mental disorders. Abstrak: Peran pemberdayaan masyarakat sangat dibutuhkan oleh keluarga atau orang dengan gangguan jiwa. Ketika tidak di berdayakan oleh lingkungan, akan memberikan dampak penurunan tingkat produktifitas. Untuk mewujudkan kesehatan mental dan kepedulian masyarakat terhadap orang dengan gangguan jiwa perlu melakukan upaya strategis dengan menyusun program promosi kesehatan mental sebagai usaha preventif dan meningkatkan pemberdayaan masyarakat untuk menunjang kesehatan mental. Bertujuan untuk mengetahui pemberdayaan masyarakat dalam meningkatkan kepedulian pada pasien dengan gangguan jiwa. Basis data bibliografi berikut dicari untuk mengidentifikasi dokumen relevan yang potensial:  Google Scholar, Pubmed, dan Proquest publikasi tahun 2017-2022. Temuan dari studi diekstraksi dan dikumpulkan, dipandu oleh Joanna Briggs Institute (JBI). Literature review menggunakan database PubMed, ProQuest dan Google Scholar. Keywords: "pemberdayaan masyarakat" "kepedulian masyarakat" "perlibatan masyarakat" "gangguan jiwa". Didapatkan total 43,253 Artikel. Hasil akhir diperoleh 12 artikel yang memenuhi syarat review. Hasill dimana pemberdayaan masyarakat berupa program atau layanan tentang kesehatan di lingkungan tempat tinggal, meningkatkan kepedulian masyarakat kepada orang dengan gangguan jiwa. Pemberdayaan yang dilakukan oleh masyarakat secara langsung seperti kampanye kesehatan mental, diskusi, pelatihan serta memberikan fasilitas serta sarana untuk menunjang  kesehatan orang dengan gangguan jiwa.